INFLUENCE SHAKER EXERCISE AND MENDELSOHN'S MANEUVER TO ABILITY SWALLOWING IN STROKE PATIENTS AT DR. M. YUNUS BENGKULU IN 2023 - Dwinda Rara Olva Rara; Erni Buston; Sahran; Noni Buston (Proceeding B-ICON, 2023)
Stroke is a condition with rapidly progressive clinical symptoms, manifested by symptoms of focal and generalized neurological deficits, lasting 24 hours or more and for no apparent reason other than damage to blood vessels, and can cause death. Objective: To determine the effect of shaker training and the Delsohn maneuver on swallowing ability in stroke patients. Method: The type of research used is a quasi-experimental design with a pretest and posttest with control group design. The research sample consisted of 44 stroke patients who experienced mild to moderate swallowing disorders with RAPIDS scores of 50-100. The sampling technique is purposive sampling data collection using the RAPIDS test questionnaire sheet. Results: The average swallowing ability of respondents before being given shaker training and the Delsohn maneuver was 73.82, after being given the intervention the average swallowing ability increased to 91.55. Shows that there is an effect of shaker exercise and the Mendelsohn maneuver on swallowing ability with a p-value of 0.001<0.05. With the characteristics of respondents based on age in the intervention group being 60 years and 59 years in the control group, the education of respondents in the intervention group was mostly high school and the control group was mostly elementary school, and the gender of the intervention group was mostly female and the control group was mostly male, while the type of intervention. Conclusion: Shaker exercise and the Mendelsohn maneuver are effective for improving swallowing ability in stroke patients.